Co-production of functional xylo-oligosaccharides and fermentable sugars from corn stover through fast and facile ball mill-assisted alkaline peroxide pretreatment. (October 2021) - Zhang, Fulong; Lan, Wu; Li, Zengyong; Zhang, Aiping; Tang, Baoling; Wang, Huihui; Wang, Xiaoying; Ren, Junli; Liu, Chuanfu
Graphical abstract: Highlights: A ball-mill assisted alkaline peroxide pretreatment process was developed. 70% of XOS alone with high yield of fermentable sugars was achieved. The pretreatment process was environmental-friendly. The mechanism of enhanced enzymatic digestibility by BAP pretreatment was revealed. Abstract: The aim of this work was to develop a feasible ball mill-assisted alkaline peroxide pretreatment followed by stepwise hydrolysis to improve the yield of xylo -oligosaccharides (XOS) and fermentable sugars. The hydrogen peroxide charge, ball-milling time, and solid-to-liquid ratio affected the compositions, particle sizes, morphology, and crystallinity of the corn stover, directly improving the following hydrolytic efficiency. The optimal pretreatment was with 0.45 g/g (H2 O2 : substrate) and 1:3 solid-to-liquid ratio (w/v) for 1.0 h ball-milling, resulting in 84.29% delignification. Physicochemical properties of the pretreated samples were characterized and their correlations to the enzymatic hydrolysis were revealed. Compared with one-step cellulase hydrolysis, the two-step xylanase-cellulase hydrolysis of the pretreated corn stover showed significant advance in preparing XOS, producing 69.65% (on the base of xylan content in pretreated sample) of XOS, along with 20.55% xylose, 68.94% glucose, and 21.15% gluco -oligosaccharides. The yield of XOS was 2–7 times higher than those in previous studies.